Implementasi Kebijakan Gerakan 7 Kebiasaan Anak Indonesia Hebat (G7KAIH) di SMAN 11 Muaro Jambi - Linatul Karomah; Masbirorotni Masbirorotni; Eddy Haryanto (CV. Global Cendekia Inti, 2026)
This study aims to analyze the implementation of the “7 Habits of Great Indonesian Children” (G7KAIH) program and to identify its supporting and inhibiting factors at SMAN 11 Muaro Jambi. This study employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the school principal, teachers, and students as research participants. The results indicate that the implementation of G7KAIH has not yet been fully optimized and remains uneven across certain behavioral aspects. Supporting factors include school leadership, institutional support, and extracurricular activities, while inhibiting factors consist of limited facilities and infrastructure, low parental involvement, and the socioeconomic conditions of students. This study highlights the importance of collaboration between schools, families, and the broader social environment in supporting the implementation of character education programs.